PERAN KAUM MUSLIM TRADISIONALIS DALAM PEMBARUAN PENDIDIKAN ISLAM DI PALEMBANG PADA ERA KOLONIAL - Ismail, Ismail (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2005)
There have been a lot of studies on the history and development of Islamic education in Indonesia conducted by various groups. At least, there are three important aspects that should be noted in this study. First, from the aspect of the region, the history of Islamic education in South Sumatera which has never been comprehensively studied since the colonial era. Second, related to theoretical assumption, the question of whether the development of the system and the modern Islamic institution in Palembang during colonial era tend to be dominated by Muslim reformers or Muslim traditionalists. Third, from the point of view of methodology which tends to be descriptive and chronological, though recently there arises an analytical approach in which the system and the institution are not seen as things that can stand on their own, but are attached to social, religious, cultural, and political aspects. It is this approach which will be used in this study. Therefore, this study will try to look into the relationship between various social changes in Palembang and the system and Islamic educational institutions in the colonial era.